The Humanistic Teacher: Towards Effective Teaching-Learning Process in the ESL Classroom - Mohd Shariff, Samsiah (1997)
The study aim ed to determine students' perceptions, to ascertain gender differences in perception and to ascertain socio-economic status (SES) groups differences in perception on how humanistic were the English language teachers (ELT) in teaching-learning process in the English as second language (ESL) classrooms. The aspects being studied were on applying the humanistic values/ non humanistic values by the ELT; instilling motivation and building self- independence among students by the ELT; applying the humanistic approaches by the ELT and the relative helpfulness of the humanistic approaches used by the ELT in the ESL classrooms. This study was conducted in fifteen secondary schools in Seremban. A total of 202 male students and 182 female students were involved in this study. A set of questionnaire was administered for data collection. Statistical analysis include frequencies, descriptive, t-test procedures and ANOVA. The frequencies distributions indicated that majority of the students had favourable perception on all the variables studied. Descriptive analysis showed students' positive perceptions on all the variables studied except for two non humanistic values of the ELT and one humanistic approach applied by the ELT. The finding also indicated that the ELT were more humanistic than non humanistic in teacher-student relationship in the ESL classrooms. t-tests revealed Significant differences in gender overall perception. Female students showed higher perception than male students in all the five variables measured. However, there was no significant difference in gender overall perception on ELT non humanistic values. Findings also showed significant differences in perception of students from different SES groups on three variables measured. The high SES group had higher perception than other SES groups on ELT humanistic values, instilling motivation among students by the ELT and the relative helpfulness of the humanistic approaches in students' language learning process. Hence, the role of the ELT is utmost importance in determining the success of English language teaching learning process.